An Overview of the Association between Schizotypy and Dopamine - Mohr, Christine; Ettinger, Ulrich (Frontiers in Psychiatry, 2014)
Schizotypy refers to a constellation of personality traits that are believed to mirror the subclinical expression of schizophrenia in the general population. Evidence from pharmacological studies indicates that dopamine is involved in the aetiology of schizophrenia. Based on the assumption of a continuum between schizophrenia and schizotypy, researchers have begun investigating the association between dopamine and schizotypy using a wide range of methods. In this article, we review published studies on this association from the following areas of work: (1) Experimental investigations of the interactive effects of dopaminergic challenges and schizotypy on cognition, motor control and behaviour, (2) dopaminergically supported cognitive functions, (3) studies of associations between schizotypy and polymorphisms in genes involved in dopaminergic neurotransmission, and (4) molecular imaging studies of the association between schizotypy and markers of the dopamine system. Together, data from these lines of evidence suggest that dopamine is important to the expression and experience of schizotypy and associated behavioural biases. An important observation is that the experimental designs, methods, and manipulations used in this research are highly heterogeneous. Future studies are required to replicate individual observations, to enlighten the link between dopamine and different schizotypy dimensions (positive, negative, cognitive disorganisation), and to guide the search for solid dopamine-sensitive behavioural markers. Such studies are important in order to clarify inconsistencies between studies. More work is also needed to identify differences between dopaminergic alterations in schizotypy compared to the dysfunctions observed in schizophrenia.